Ice Jam at the Rio Blanco Diversion Weir on the White River in Colorado: A Case Study of In-Stream Structures and Ice - Tuthill, Andrew M. (2008)
In-stream structures constructed of natural materials are increasingly popular on US rivers. Examples include rock weirs that provide an aesthetic means of pooling and diverting flow for irrigation and lake filling. Though considerable progress has been made in the design and construction of these soft engineering structures, most applications to date have been on rivers that are unaffected by ice. Recent experience shows that the presence of ice can have unexpected and possibly negative results. This report presents a case study of a rock diversion weir that caused a freezeup ice jam, channel shifting, and upstream flooding. The event is described and its causes analyzed. Preliminary guidance is offered on designing against similar ice problems when locating these new types of structures on rivers with ice. The original document contains color images.